A new archosauriform reptile with distinctive teeth from the Middle Triassic (Ladinian) of Germany. Issue 1 (2nd January 2020) - Sues, Hans-Dieter; Schoch, Rainer R.; Sobral, Gabriela; Irmis, Randall B.
ABSTRACT: Skeletal remains of a small reptile with a distinctive dentition from the Lower Keuper (Erfurt Formation; Middle Triassic, Ladinian) of the Schumann quarry near Eschenau, in the municipality of Vellberg in Baden-Württemberg, Germany, represent a new taxon of non-archosaurian archosauriforms, Polymorphodon adorfi . It is diagnosed by various craniodental autapomorphies, including mesial and distal carinae of labiolingually flattened maxillary and dentary tooth crowns with large, somewhat hook-shaped denticles aligned at distinct angle to apicobasal axis of tooth crown; premaxilla with long, leaf-shaped posterodorsal process that is slightly longer than body of element; presence of prominent lateral fossa on premaxilla anteroventral to external narial fenestra; premaxilla with five gently recurved, conical teeth; medial surface of maxilla with distinct ledge above the interdental plates; and maxilla and dentary with distinctly heterodont dentition. Phylogenetic analysis recovered Polymorphodon adorfi in a position crownward of Erythrosuchus africanus but in an unresolved polytomy with derived non-archosaurian archosauriforms such as Proterochampsidae and Euparkeria capensis and with Archosauria. The maxillary and dentary teeth of Polymorphodon adorfi differ from those of other non-archosaurian archosauriforms and indicate a different, possibly omnivorous diet, suggesting that these reptiles were more diverse in terms of feeding habits than previously assumed.